2020
DOI: 10.1371/journal.pone.0241262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of monocyte distribution width and neutrophil-to-lymphocyte ratio for distinguishing COVID-19 and influenza from other upper respiratory tract infections: A pilot study

Abstract: The coronavirus disease 2019 (COVID-19) has become a pandemic. Rapidly distinguishing COVID-19 from other respiratory infections is a challenge for first-line health care providers. This retrospective study was conducted at the Taipei Medical University Hospital, Taiwan. Patients who visited the outdoor epidemic prevention screening station for respiratory infection from February 19 to April 30, 2020, were evaluated for blood biomarkers to distinguish COVID-19 from other respiratory infections. Monocyte distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 36 publications
7
45
0
1
Order By: Relevance
“…This suggestion seems consistent with COVID-19 studies highlighting the predictive role of neutrophils-to-lymphocyte ratio (NLR) and other similar cell ratios, based on combination of myeloid and lymphoid subsets [29][30][31]. Very recently, a diagnostic test using NLR and MDW has been demonstrated to accurately distinguish COVID-19 from in uenza and common upper respiratory tract infections in patients with suspected symptoms (AUC: 0.84; MDW threshold, ≥20) [32].…”
Section: Discussionsupporting
confidence: 84%
“…This suggestion seems consistent with COVID-19 studies highlighting the predictive role of neutrophils-to-lymphocyte ratio (NLR) and other similar cell ratios, based on combination of myeloid and lymphoid subsets [29][30][31]. Very recently, a diagnostic test using NLR and MDW has been demonstrated to accurately distinguish COVID-19 from in uenza and common upper respiratory tract infections in patients with suspected symptoms (AUC: 0.84; MDW threshold, ≥20) [32].…”
Section: Discussionsupporting
confidence: 84%
“…Only two studies investigated the NLR levels in COVID-19 compared to In uenza. One found no difference, and the other found that NLR was signi cantly lower in the COVID-19 patients (median of 2.6), as was described in our report 32,44 . In all reports, as in ours, CRP levels at admission were similar across the viruses.…”
Section: Discussionsupporting
confidence: 78%
“…Reviewing the literature we found few small -scale studies comparing laboratory parameters of adult patients with COVID- 19 and In uenza 32,42,43 and none compared with RSV. Only two studies investigated the NLR levels in COVID-19 compared to In uenza.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For adult COVID-19 patients, a small study showed a higher level of neutrophil count in patients admitted to ICU than in those not [14]. NLR is useful in diagnosing in uenza virus infections and in discriminating other respiratory infections [22,23]. In COVID-19 patients, elevated NLR is an independent factor for poor clinical outcome [24,25].…”
Section: Discussionmentioning
confidence: 99%